An Investigation of Forming Analysis of Fibre-Metal Laminates through Experimental and Finite Element Analysis - Sivakumar, Dhar Malingam (2011)
Fibre Metal Laminates (FML) systems are a hybrid material consisting of alternating layers of metal and fibre-reinforced polymer composite. Their sandwich nature and combination of different materials afford them good impact and fatigue properties as well as superior specific properties such as strength to weight and stiffness to weight ratio. The present paper discusses the effect of process parameters in the stamp forming of domes for a class of polypropylene based FML material systems. This study looks at the effect of preheat temperature, blank holder force and feed rate. A Design of Experiment (DOE) methodology using an L9 array with three parameters at three levels was used to elucidate the effect the process variables on the formability. The correct choice of the process parameters was deemed to be important for achieving high quality of the parts manufactured. Comparisons between FML and monolithic aluminium revealed that FML possess better formability characteristics than monolithic aluminium. Moreover FML gives a 27% weight reduction compared to monolithic aluminium. Comparison between FML and monolithic aluminium surface strain results show FML system having a more uniform strain distribution further enhancing the quality of the final part using this class of material. Furthermore the work required to form FML is 30% less than for monolithic aluminium. The results obtained in the present study shows FML systems have the potential to be adapted to high volume production technique of stamp forming.